Social influence and MNE strategic response to political risk: A global network approach - Cannizzaro, Anthony P (Journal of International Business Studies, 2020)
According to the conventional view of MNE–host country relations, MNEs faced with political risk condition their strategic responses on each party’s relative power positions – or bargaining influence. Drawing insight from network theory, institutional theory, and international relations research, I argue that firm sensitivity to political risk is contingent upon a complementary concept: social influence. Social influence arises through the mutual embeddedness of MNE and host government in a complex global network of nations. To test my hypotheses, I construct a global network of trade relations that I combine with a unique transaction-level dataset from the global petroleum industry. My results demonstrate that social influence, as modeled by home–host structural equivalence, moderates the effects of political risk. Further, my findings provide support for a conceptual and empirical distinction between social influence and the traditional bargaining influence examined in the literature.